Dreams, Danger and Escapism in Stevenson’s Treasure Island: A Literary Reflection - Soxibova U. N. (Development in Language Studies, 2025)
Robert Louis Stevenson’s Treasure Island is not merely a children’s adventure novel but a deep exploration of escapism and the struggle between dreams and reality. This paper analyzes how Stevenson constructs a narrative that allows readers to immerse themselves in a thrilling world of pirates, treasure maps, and high-seas adventures while simultaneously grappling with the harsh truths of life. The study explores the psychological impact of escapism on both the protagonist, Jim Hawkins, and the readers, highlighting how the novel reflects a universal human desire to escape mundane reality in pursuit of excitement and purpose. The discussion also examines Stevenson’s use of vivid storytelling and character development to balance the allure of adventure with the inevitable confrontation of real-world dangers.